LiDAR Sensor: Applications in Agriculture - Debangshi, Udit (Chronicle of Bioresource Management, 2023)
Agriculture is one of the oldest and primitive occupations. However, this sector is currently facing number of challenges, including population growth, high production costs, urbanisation and environmental degradation. According to the Food and Agriculture Organization (FAO), by 2050, we need to produce 60% more food to feed a world population of 9.3 billion. As a result, there is an urgent need for some sustainable, resource-efficient technologies to combat these issues, among which, LiDAR sensor is one of better options. LiDAR, which stands for Light Detection and Ranging, is a remote sensing method that measure variable distances of the Earth by using light in the form of a pulsed laser. LiDAR can smartly improve the agriculture system with 3D modelling, yield forecasting, soil type determination and phenomics study. Even in difficult weather and lighting conditions, it provides precise 3D measurement. Thus, this technology is preparing the agricultural sector for the future.